The Role of Vitamin D in Inflammatory Bowel Disease – Assessing Therapeutic and Preventive Potential of Supplementation and Food Fortification - Leskovar, Dunja (Food Technol Biotechnol, 2018)
Inflammatory bowel diseases are a group of chronic inflammatory conditions that affect gastrointestinal tract due to inapt and continuous immune activation in response to a myriad of predisposing factors (most notably genetics, environmental impact and gut microbiota composition). It has been shown that vitamin D status can also play a role in the disease pathogenesis, as its deficiency is commonly observed in two major forms of inflammatory bowel diseases – Crohn’s disease and ulcerative colitis. Mounting evidence supports the concept of intricate relationship between gut dysbiosis and vitamin D metabolism, while suboptimal levels of this vitamin have been linked to increased clinical disease relapse rates, inadequate response to drugs, as well as decreased quality of life in patients with Crohn’s disease and ulcerative colitis. Consequently, the pertinent question is whether increased vitamin D supplementation and (on a population level) food fortification may bring significant benefit to the affected individuals. In this short review we discuss the synthesis, functions, status and food sources of vitamin D, appraise biotechnological facets of vitamin D status analysis and food fortification, and concentrate on novel developments in the field that describe its influence on intestinal microbiota and inflammatory bowel disease.